Respuesta :
Answer:
Step-by-step explanation:
g(x)= -2 x^2 + 3 x - 5
g(-2) = -2 . (-2)^2 + 3. (-2) - 5 = -2 . 4 - 6 - 5 = - 8 - 6 - 5 = - 19
g(0) = -2 . (0)^2 + 3 . 0 - 5 = -2 . 0 + 0 - 5 = 0 + 0 - 5 = - 5
g(3) = -2 . (3)^2 + 3 . (3) - 5 = -2 . 9 + 9 - 5 = -18 + 9 - 5 = - 14
The value of g(x) is the input values are –2, 0, and 3 are -19, -5 and -14
Functions and values
Given the following function
g(x) = –2x² + 3x – 5
For the input value of -2
g(-2) = –2(-2)² + 3(-2) – 5
g(-2) = -8 - 6 - 5
g(-2) =-19
If the value of x is 0
g(0) = –2(0)² + 3(0)– 5
g(0) = -5
If the vaue of x is 3
g(3) = –2x² + 3x – 5
g(3) = -2(3)² + 3(3)– 5
g(3) =-18 + 9 - 5
g(3) = -14
Hence the value of g(x) is the input values are –2, 0, and 3 are -19, -5 and -14
Learn more on function and values here: https://brainly.com/question/10439235
#SPJ2